2002
DOI: 10.1016/s1534-5807(02)00267-8
|View full text |Cite
|
Sign up to set email alerts
|

An Immune-Responsive Serpin Regulates the Melanization Cascade in Drosophila

Abstract: In arthropods, the melanization reaction is associated with multiple host defense mechanisms leading to the sequestration and killing of invading microorganisms. Arthropod melanization is controlled by a cascade of serine proteases that ultimately activates the enzyme prophenoloxidase (PPO), which, in turn, catalyzes the synthesis of melanin. Here we report the biochemical and genetic characterization of a Drosophila serine protease inhibitor protein, Serpin-27A, which regulates the melanization cascade throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
270
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 309 publications
(275 citation statements)
references
References 36 publications
3
270
2
Order By: Relevance
“…De novo synthesis of melanin in response to tissue damage occurs through the melanization cascade, a series of enzymatic reactions involving serine proteases that activate phenol oxidase (PO), which catalyzes the conversion of phenolic substrates to quinones, which then polymerize to form melanin (32). The melanization reaction in the hemolymph can be blocked by mutations in the Drosophila gene Black cells (Bc), which encode PO, and Bc/Bc larvae do not have PO activity (33). To determine if the black spots in the Drosophila eyes expressing CHMP2B Intron5 are melanin deposits, we crossed GMR-Gal4, UAS-CHMP2B Intron5 flies with Bc mutant flies.…”
Section: Gmr-gal4; Uas-chmp2bmentioning
confidence: 99%
“…De novo synthesis of melanin in response to tissue damage occurs through the melanization cascade, a series of enzymatic reactions involving serine proteases that activate phenol oxidase (PO), which catalyzes the conversion of phenolic substrates to quinones, which then polymerize to form melanin (32). The melanization reaction in the hemolymph can be blocked by mutations in the Drosophila gene Black cells (Bc), which encode PO, and Bc/Bc larvae do not have PO activity (33). To determine if the black spots in the Drosophila eyes expressing CHMP2B Intron5 are melanin deposits, we crossed GMR-Gal4, UAS-CHMP2B Intron5 flies with Bc mutant flies.…”
Section: Gmr-gal4; Uas-chmp2bmentioning
confidence: 99%
“…The soluble proteins of plasma, hemocyte lysate, and fat body were precipitated with trichloroacetic acid and subjected to SDS-PAGE and then immunoblotting with affinity-purified Hd-PGRP-1 and Hd-PGRP-2 antibodies, respectively. Previously it was reported that insect proPO system induced the activation of serine protease zymogen to active serine protease during 1,3-␤-D-glucan-dependent proPO activation (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)30). To explore the existence of serine protease activity during 1,3-␤-D-glucan-specific proPO activation, we examined the amidase activity in the presence of 1,3-␤-D-glucan and Ca 2ϩ by using commercially available trypsin substrate, Boc-PheSer-Arg-MCA.…”
Section: 3-␤-d-glucan and Pgn Binding Assay-mentioning
confidence: 99%
“…This enzyme produces toxic compounds to microorganisms by oxidizing phenols to melanin, and it also participates in the sclerotization of the cuticle, which is vital for the survival of insects (18). Many reports have been published about the proPO of the invertebrate and its activation mechanism (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). A key question regarding the proPO activation system is how pattern recognition molecules can induce activation of the system in response to microbial infection.…”
mentioning
confidence: 99%
“…1) (Ashida and Brey, 1997;Sugumaran, 2002;Nappi and Christensen, 2005). In vitro and in vivo studies demonstrated that PO generates quinones for melanogenesis (Jiang et al, 1997;De Gregorio et al, 2002a) and leads to changes in the physical properties of hemolymph clot through protein crosslinking (Bidla et al, 2005). Cuticle tanning (i.e.…”
Section: Introductionmentioning
confidence: 99%